2020
DOI: 10.1002/pen.25523
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylic acid) hydrogel microparticles fabricated with silver nanoparticles: synthesis, characterization, and catalytic applications

Abstract: This work narrates the synthesis of poly (acrylic acid) hydrogel microparticles (PAAHMPs), fabrication of silver nanoparticles (AgNPs) inside the structure of the prepared PAAHMPs and catalytic applications of PAAHMPs fabricated with AgNPs (PAAHMPs/AgNPs). The PAAHMPs were prepared by inverse suspension polymerization technique while fabrication of AgNPs was carried out by chemical reduction method using sodium borohydride (NaBH 4) as reducing agent. The identification of functional groups in bare PAAHMPs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Considering that the contact with bacteria has been reported to be pivotal for the hydrogels to show antibacterial activity, this decent antibacterial property of SA 3 hydrogel can be mainly attributed to the presence of methacrylic acid groups and its direct contact with bacteria in this work. 33,41,42 Signicantly, the GA/SA 3 DN hydrogel exhibited high bacteriostatic ratios beyond 99.9% against E. coli and S. aureus bacteria beneting from the synergetic antibacterial effect of SA and GA hydrogels. These results demonstrated excellent antibacterial ability of GA/SA 3 DN hydrogels.…”
Section: Antibacterial Propertymentioning
confidence: 97%
“…Considering that the contact with bacteria has been reported to be pivotal for the hydrogels to show antibacterial activity, this decent antibacterial property of SA 3 hydrogel can be mainly attributed to the presence of methacrylic acid groups and its direct contact with bacteria in this work. 33,41,42 Signicantly, the GA/SA 3 DN hydrogel exhibited high bacteriostatic ratios beyond 99.9% against E. coli and S. aureus bacteria beneting from the synergetic antibacterial effect of SA and GA hydrogels. These results demonstrated excellent antibacterial ability of GA/SA 3 DN hydrogels.…”
Section: Antibacterial Propertymentioning
confidence: 97%
“…Similar observations were reported by Han et al and Bibi et al 32,33 It is a well-known fact that polymer hydrogels exhibit porous nature while AgNPs exhibit crystalline nature and a composite prepared by fabricating AgNPs in a polymer hydrogel network possess both the amorphous and crystalline properties. 23 The XRD patterns of BMG and AgNPs-MG are shown in Fig. 1(b).…”
Section: Characterization Of Bmg and Agnps-mgmentioning
confidence: 99%
“… 22 If the AgNPs fabricated in a suitable microgel and the system is used as catalyst then recovery of this catalyst from a catalytic reaction medium can be done easily by simple filtration or quick centrifugation process. 23 Timo et al 24 fabricated AgNPs in a microgel system and found it as temperature sensitive catalyst for the reduction of 4-NP. Lazaros et al 25 also reported the synthesis of AgNPs in a microgel system and their application as an efficient catalyst in the reduction of 4-NP.…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, compared with pure silver nanoparticles and pure copolymer, nano-silver loaded poly(styrene-co-acrylic) composites can increase the affinity between silver and the nitrile group on the surface of the microspheres, thereby depositing on the porous polymicrospheres with surface functions. 15 Composite microspheres can effectively prevent the accumulation of metal nanoparticles and improve the catalytic stability and have a wider range of applications. 16 It is believed that the carboxyl group in acrylic acid leads to an increase in the mobility of silver ions in the copolymer, resulting in enhanced antibacterial surface activity.…”
Section: Introductionmentioning
confidence: 99%